Surgeon-Performed Intraoperative Peripheral Nerve Blocks and Periarticular Infiltration During Total Hip and Knee Arthroplasty: A Critical Analysis Review. Issue 11 (23rd November 2022) - Drapeau-Zgoralski, Véronique; Bourget-Murray, Jonathan; Hall, Brandon; Horton, Isabel; Dervin, Geoffrey; Duncan, Kenneth; Addy, Keith; Garceau, Simon
Abstract : ➢ Surgeon-performed intraoperative peripheral nerve blocks may improve operating room efficiency and reduce hospital resource utilization and, ultimately, costs. Additionally, these blocks can be safely performed intraoperatively by most orthopaedic surgeons, while only specifically trained physicians are able to perform ultrasound-guided peripheral nerve blocks. ➢ IPACK (infiltration between the popliteal artery and capsule of the knee) blocks are at least noninferior to periarticular infiltration when combined with an adductor canal block for analgesia following total knee arthroplasty. ➢ Surgeon-performed intraoperative adductor canal blocks are technically feasible and offer reliable anesthesia comparable with ultrasound-guided blocks performed by anesthesiologists. While clinical studies have shown promising results, additional Level-I studies are required. ➢ A surgeon-performed intraoperative psoas compartment block has been described as a readily available and safe technique, although there is some concern for femoral nerve analgesia, and temporary sensory changes have been reported.